2015
DOI: 10.18632/oncotarget.6386
|View full text |Cite
|
Sign up to set email alerts
|

Doublecortin-like kinase 1 expression associates with breast cancer with neuroendocrine differentiation

Abstract: Doublecortin-like kinase 1 (DCLK1), a microtubule associated kinase, has recently been proposed to be a putative marker for stemness and adverse prognosis in gastrointestinal cancers. However, it is not clear whether the protein also plays similar roles in breast cancer. Here, the expression of DCLK1 was analyzed in a large cohort of invasive breast cancers (IBC) by immunohistochemistry. DCKL1 was associated with favorable clinico-pathologic features, namely lower histologic grade, absence of lymphovascular in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…Thus, O'Connell and colleagues were able to reconcile the apparent contradictory findings of widespread epigenetic silencing of the Dclk1C gene on one hand, and the clear functional importance of the transcript in a broad variety of cancers on the other. 41 Accordingly, Dclk1 expression has been observed in neuroendocrine tumors of the mammary gland and the rectum, 42,43 consistent with the known expression of Dclk1 in neuronal and enteroendocrine cells, but no specific role for Dclk1 in these tumors has been suggested so far. Finally, the relevance of Dclk1 expression in esophageal cancer is presently unclear, 44 but the cells seem to correlate with an increased progression to cancer in a murine model and human patients.…”
Section: Functional Relevance Of Dclk1 Expression In Malignancymentioning
confidence: 53%
“…Thus, O'Connell and colleagues were able to reconcile the apparent contradictory findings of widespread epigenetic silencing of the Dclk1C gene on one hand, and the clear functional importance of the transcript in a broad variety of cancers on the other. 41 Accordingly, Dclk1 expression has been observed in neuroendocrine tumors of the mammary gland and the rectum, 42,43 consistent with the known expression of Dclk1 in neuronal and enteroendocrine cells, but no specific role for Dclk1 in these tumors has been suggested so far. Finally, the relevance of Dclk1 expression in esophageal cancer is presently unclear, 44 but the cells seem to correlate with an increased progression to cancer in a murine model and human patients.…”
Section: Functional Relevance Of Dclk1 Expression In Malignancymentioning
confidence: 53%
“…In addition, IHC results showed that DCLK1 is upregulated in stage II-III tumors compared to normal kidney and stage I tumors [15]. Conversely, DCLK1 was found to be associated with favorable clinicopathologic features and a good prognostic factor in breast cancer, particularly in invasive breast cancers with neuroendocrine differentiation (IBC-NED) [14]. These contrasting results with regard to tumor-promoting roles in gastrointestinal cancers suggest different functional roles for DCLK1 in different type of cancers.…”
Section: Discussionmentioning
confidence: 98%
“…Accumulating evidence suggests that CSCs are responsible for cancer metastasis, recurrence and radio/chemo-resistance [36][37][38], and previous reports demonstrate that DCLK1 can mark CSCs in gastrointestinal and other cancers [12][13][14]. A recent study revealed that DCLK1 is essential for the invasive and metastatic properties of CSCs in human pancreatic cancer and that it might be a promising therapeutic target [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, Nakanishi et al demonstrated that ablation of DCLK1 in murine models resulted in tumor shrinkage without damage to the normal intestine and postulated that DCLK1 was a marker for CSC but not normal intestinal cells (17). In the clinical setting, DCLK1 expression has been reported in tumors of the esophagus, pancreas, kidney, breast, and colon (18)(19)(20)(21)(22)(23)(24). A few studies have demonstrated the association of DCLK1 expression with poor prognosis of colorectal cancer patients treated without preoperative therapy (18,19).…”
mentioning
confidence: 99%